Impure altruism and other donor attraction factors: A study based on a database of non-government organizations (NGOs) in the Philippines - Renato E. Reside (University of the Philippines, School of Economics (UPSE), 2017)
This study uses panel data on a sample of non-government organizations (NGOs) to estimate the factors that motivate donors to contribute to them. The results of empirical estimation suggest that a mix of conventional and tax factors influence donors. The results are consistent with the hypothesis that donors are not totally altruistic and are motivated by private benefits from donating. There is strong evidence that the private benefits come more from tax concessions from the act of donating. Hence, tax planning and arbitrage motives, more than 'warm glow' factors influence donor contributions.
Keywords: C80; D64; H26; 330; Nonprofit corporations; donations; altruism